Impact of Covid-19 on Profitability (Case Study on The Health Subsector Listed on Indonesia Stock Exchange) - Reta Rosita; Muhammad Wadud; Endah Dewi PurnamaSari (International Journal of Community Service & Engagement, 2022)
This study aims to explore the impact of the Covid-19 pandemic on the profitability of health subsector companies listed on the Indonesia Stock Exchange. The aspects analyzed in this study were gross profit margin, net profit margin, return on assets, and return on equity. Samples were selected deploying purposive sampling technique. Data of 9 companies were collected from the investment gallery of the Indonesia Stock Exchange (BEI). This study implemented a series of paired sample t-test to analyze data before and during the Covid-19 pandemic. The results evidenced that there is no significant difference between before and during the Covid-19 pandemic for each aspect of gross profit margin, net profit margin, return on assets, return on equity.